Thermodynamic study of Liquid-Liquid Equilibria in Ternary System of Methanol, Toluene, and Hexane (Comprehensive Journal of Science, 2026)
Liquid- liquid equilibrium (LLE) data are essential for the design and optimization of liquid- liquid extraction processes in chemical and petrochemical industries. In this work, experimental LLE data for the ternary system {Methanol + toluene +  hexane}  were investigated at 298, 303 ,308 and 313K  under atmospheric pressure 101.3 KPa, The equilibrium composition of the coexisting liquid phases were determined and used to construct bimodal curves and tie-line data for the system. Distribution coefficient and separation factors were calculated in order to evaluate the extraction performance of toluene for separating methanol from hexane. The reliability of the experimental tie-line data was examined using Othmer-Tobias and Hand correlations. The experimental data were correlated using the NRTL and UNIQUAC thermodynamic models. Both models successfully represented the phase equilibrium behavior of the system, with the UNIQUAC model showing slightly better agreement with the experimental results. The average root mean square deviation (RMSD) values were approximately 1.013% for UNIQUAC and 1.189%for NRTL.
Keywords: Liquid-liquid equilibrium; Methanol; Toluene; Hexane; Thermodynamic modeling; UNIQUAC; NRTL